Aplikasi Pemesanan Cetak Foto Berbasis Web - Ali Djamil (Informatics Engineering Department-UWKS, 2019)
Human world and information is an important part for human life now this website and internet is a medium of delivery of information or media campaigns effective and efficient, with the internet network we can explore where and whenever connected to the internet network. The development of the internet world is now very fast and has been in great demand for people to utilize the virtual world in every activity in the real world. Promoting photo printing services using the website will be more profitable, can also be a development process and can save costs. Photo and choice options. Photos without having to. The results expected in this research is a web-based photo ordering application can be an alternative in the process of ordering print photos online without customers having to visit directly to the photo printing studio.